Glutinous rice ball filled with banana and chocolate and coated with nuts / Siti Aishah Ahmad Zaki, Siti Amni Najwa Zahaludin and Nur ‘Amira Hamid - Ahmad Zaki, Siti Aishah; Zahaludin, Siti Amni Najwa; Hamid, Nur ‘Amira (Faculty of Plantation and Agrotechnology, 2023)
The traditional Indonesian snack known as Klepon / “Buah Melaka” has gained popularity throughout south- east Asia. According to tradition, glutinous rice flour - one of the most important and fundamental components of the majority of Indonesia's traditional snacks is typically used to make Klepon/ “Buah Melaka”. Therefore, the purpose of this study is to progress and improve Klepon / “Buah Melaka” by changing the ingredients in the expectation that it would increase the product's attractiveness. The modification done is by incorporating the glutinous rice ball filled with banana and chocolate coated with nuts. To see the success outcome of this research, we made several experiments using different ratios and measurements of the ingredients. The method of data collection used here by making questionnaire feedback from people around us.